Clinical correlates of perivascular adipose tissue in coronary artery disease and obesity - Upadhaya, Sunil; Pandey, Amitabh C.; Wiley, Jose; Le Jemtel, Thierry H. (Frontiers in Physiology, 2025)
The adipose tissue surrounding the arterial and venous vasculature and microvasculature affects vascular reactivity and pathology, particularly when perivascular adipose tissue (PVAT) accumulates in overweight and obese states. In the absence of convenient techniques to measure local blood flow and adipose tissue volume, perivascular adipose tissue-related alterations are barely considered in clinical settings. Furthermore, perivascular adipose tissue accumulation frequently coexists with obesity, and obesity alone leads to functional and structural vascular alterations. The proximity of epicardial adipose tissue (EAT) to the coronary arteries provides a unique opportunity to study the effects of perivascular adipose tissue on vascular pathology and reactivity. As coronary atherosclerotic plaque inflammation contributes to the inflammatory response of the surrounding adipose tissue, pericoronary adipose tissue attenuation may predict the risk of acute coronary events. Finally, perivascular adipose tissue accumulation may mediate obesity-associated regional subclinical left ventricular dysfunction in the absence of coronary artery disease.